PEMBELAJARAN TARI KEMBANG MELINTING PADA EKSTRAKULIKULER TARI DI SMAS BINA MULYA GADINGREJO - Mustika , I Wayan; Soleh, Safei; Prayogi, Rahmat (FKIP Universitas Lampung, 2023)
This study formulates the problem of how to learn the melinting flower dance. This study aims to describe the process of learning the melinting flower dance, describe the range of motions of the melinting flower dance and the methods used by trainers in teaching dance. The theory used is behavioristic theory, this type of research is qualitative which produces descriptive data. The techniques used in collecting data are: observation, interviews, documentation and practice tests. Sources of data were obtained from arts and culture teachers, creators of the melinting flower dance, dance trainers and seven students of SMAS Bina Mulya Gadingrejo. The instrument used is a trainer's observation sheet. Data analysis used is data reduction, data presentation, and drawing conclusions. The results of the learning process for the melinting dance for six meetings were obtained through practical tests with good, sufficient and poor criteria.